The Role of Vitamin D Deficiency in Children With Recurrent Wheezing—Clinical Significance - Feketea, Gavriela; Bocsan, Corina I.; Stanciu, Luminita Aurelia; Buzoianu, Anca Dana; Zdrenghea, Mihnea Tudor (Frontiers in Pediatrics, 2020)
Recurrent wheezing (RW) in infancy is one of the most frequent reasons for parents to consult health care providers and creates a huge global burden. Clinical course of RW is difficult to predict, also which infants will progress to asthma, since no valid biomarkers have been established. Identification of those infants with RW who are at risk of further recurrences and/or severe acute respiratory tract infection (ARTI) could help pediatricians to improve their therapeutic decisions. Increasing research interest is focused on the extra-skeletal actions of vitamin D (VD) and the clinical impact of VD insufficiency/deficiency. As VD deficiency could be a risk factor for causing RW in children, measurement of their serum level of 25-hydroxycholecalciferol [25(OH)D] is recommended. In the case of deficiency, VD should be administered in doses depending on age for at least 6 weeks, until achievement of normal blood 25(OH)D level, followed by supplementation as long as exposure to sun is inadequate. Higher doses of VD given in an attempt to prevent asthma development appear to be of no additional benefit. In children with severe ARTI, VD level is recommended to be assess.